The experience of foreignness in The Double Book by Dimitris Hatzis - Efi Petkou (Cahiers Balkaniques)
Dimitris Hatzis’ novel, The Double Book (1976), a work of migrant literature, is an interweave of paradigmatic stories of Greeks who emigrate and reshape their identity, after leaving behind their life in their native land. The experience of foreignness is experienced both by characters in the book who consciously choose to uproot themselves from their homeland and struggle to adapt to the unfamiliar cultural environments of foreign lands, while battling against nostalgia, alienation and loneliness, and also by others who are forced to leave their provincial birthplace and end up feeling alien to themselves. The present study attempts to view these stories as the axes of a modern narrative about the “romeiko” and its lost generations, which presents different but equally painful experiences of expatriation and the aspects of the hard struggle for survival in an unwelcoming land. Taking into account postmodern theoretical approaches to migrant writing which describe it as “writing between the two” (“écriture de l’entre-deux”), it examines both the nostalgic recollections of a fragmented individual and collective memory of the recent or distant past, linked to the longing to return, and the ideological and ontological problems created by experiencing “déterritorialisation” and a sense of not belonging (“désappartenance”). The study also contemplates the marginal psychological states that arise during the process of acculturation, which are caused by difficulties in communication or by the subjective and national identity crisis of the immigrants. Nevertheless, hope of an interdependent multi-ethnic world emerges at the end of the novel, and gives rise to a humanist reflection on the need to form intercultural consciences and open “rhizomatic identities” (“identités rhizomatiques”) in contemporary multicultural communities.